Aesthetic Emotions Reconsidered. (2nd March 2020) - Fingerhut, Joerg; Prinz, Jesse J
Abstract: We define aesthetic emotions as emotions that underlie the evaluative assessment of artworks. They are separated from the wider class of art-elicited emotions. Aesthetic emotions historically have been characterized as calm, as lacking specific patterns of embodiment, and as being a sui generis kind of pleasure. We reject those views and argue that there is a plurality of aesthetic emotions contributing to praise. After presenting a general account of the nature of emotions, we analyze twelve positive aesthetic emotions in four different categories: emotions of pleasure, contemplation, amazement, and respect. The emotions that we identify in each category, including feelings of fluency, intrigue, wonder, and adoration, have been widely neglected both within aesthetics and in emotion research more broadly.